Charge-coupled device speckle observations of binary stars with the WIYN telescope. v. measures during 2001-2006 - Horch, Elliott P.; van Altena, William F.; Cyr, William M.; Kinsman-Smith, Lori; Srivastava, Amit; Zhou, Jing (The Astronomical Journal, 2008)
A total of 1067 speckle observations of 345 binary stars are presented. Of these, 161 are double stars first resolved by Hipparcos, 17 are resolved for the first time in the observations presented here, and 21 are stars previously discovered by our program and reported in earlier papers in the series. In 947 cases, a magnitude difference is reported along with the relative astrometry. When comparing to systems with very well-known orbits, we find that the root mean square (rms) deviation in separation residuals is 2.81 0.28 mas, and the rms deviation in position angle residuals is 0.88 0.07°. The magnitude difference measures show no significant deviation from Hipparcos photometry, and have average standard deviation of approximately 0.10 mag as judged from repeat observations. Five important systems discovered by Hipparcos are discussed. © 2008. The American Astronomical Society. All rights reserved..
56 citations (Crossref) [2023-10-31] Citation Key Alias: pop00069 tex.type: [object Object]
Keywords: Astrometry; Binaries: visual; Techniques: interferometric; Techniques: photometric; dept.phy; peer-reviewed

Observations of binary stars with the differential speckle survey instrument. i. instrument description and first results - Horch, Elliott P.; Veillette, Daniel R.; Gallé, Roberto Baena; Shah, Sagar C.; O'Rielly, Grant; van Altena, William F. (The Astronomical Journal, 2009)
First results of a new speckle imaging system, the Differential Speckle Survey Instrument, are reported. The instrument is designed to take speckle data in two filters simultaneously with two independent CCD imagers. This feature results in three advantages over other speckle cameras: (1) twice as many frames can be obtained in the same observation time which can increase the signal-to-noise ratio for astrometric measurements, (2) component colors can be derived from a single observation, and (3) the two colors give substantial leverage over atmospheric dispersion, allowing for subdiffraction-limited separations to be measured reliably. Fifty-four observations are reported from the first use of the instrument at the Wisconsin-Indiana-Yale-NOAO 3.5 m Telescope9The WIYN Observatory is a joint facility of the University of Wisconsin-Madison, Indiana University, Yale University, and the National Optical Astronomy Observatories. in 2008 September, including seven components resolved for the first time. These observations are used to judge the basic capabilities of the instrument. © 2009. The American Astronomical Society. All rights reserved.
99 citations (Crossref) [2023-10-31] Citation Key Alias: pop00033 tex.type: [object Object]
Keywords: astrometry; binaries: close; binaries: visual; dept.phy; instrumentation: high angular resolution; instrumentation: interferometers; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Ccd speckle observations of binary stars with the wiyn telescope. vi. measures during 2007-2008 - Horch, Elliott P.; Falta, David; Anderson, Lisa M.; DeSousa, Michael D.; Miniter, Craig M.; Ahmed, Tasmia; van Altena, William F. (The Astronomical Journal, 2009)
Results of 974 speckle observations of 546 binary stars are presented. Observations were obtained at the WIYN 3.5 m Telescope at Kitt Peak National Observatory during the time interval from 2007 January to 2008 June. In all cases, the relative separation and position angle of the components are measured, and the magnitude difference is determined in 809 cases. The precision of the results as judged from repeat observations and objects with very well-determined orbits is similar to previous papers in this series, namely ∼ 3 mas in separation and <1° in position angle in most cases. Similarly, the photometric precision remains consistent with previous WIYN speckle data, on average ∼ 0.1 mag per observation. Six systems of special interest are discussed. © 2010. The American Astronomical Society. All rights reserved.
58 citations (Crossref) [2023-10-31] Citation Key Alias: pop00066 tex.type: [object Object]
Keywords: Binaries: visual; Techniques: high angular resolution; Techniques: interferometric; Techniques:Photometric; dept.phy; peer-reviewed